2019
DOI: 10.1016/j.xphs.2018.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Model-Based Drug Development in Pulmonary Delivery: Pharmacokinetic Analysis of Novel Drug Candidates for Treatment of Pseudomonas aeruginosa Lung Infection

Abstract: Antibiotic resistance is a major public health threat worldwide. In particular, about 80% of cystic fibrosis patients have chronic Pseudomonas aeruginosa (PA) lung infection resistant to many current antibiotics. We are therefore developing a novel class of antivirulence agents, quorum sensing inhibitors (QSIs), which inhibit biofilm formation and sensitize PA to antibiotic treatments. For respiratory conditions, targeted delivery to the lung could achieve higher local concentrations with reduced risk of adver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 40 publications
3
16
0
Order By: Relevance
“…Previous analogues of the compounds have been shown to be rapidly absorbed when given as a solution formulation. 11 The results in the present study showed that these compound analogues were easily absorbed even when given as a suspension formulation. Such rapid absorption has also been reported with other antimicrobial agents.…”
Section: Discussionsupporting
confidence: 51%
See 4 more Smart Citations
“…Previous analogues of the compounds have been shown to be rapidly absorbed when given as a solution formulation. 11 The results in the present study showed that these compound analogues were easily absorbed even when given as a suspension formulation. Such rapid absorption has also been reported with other antimicrobial agents.…”
Section: Discussionsupporting
confidence: 51%
“…The relatively simple formulation vehicle used in this study was established previously to improve solubility of the compound series with excipients that have been shown to be suitable for lung administration. 11 , 20 22 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations